2020
DOI: 10.1097/ico.0000000000002618
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Contamination Rate and Microorganism Evaluation in Organ-Cultured Human Corneas: A 14-Year Review From a French Regional Eye Bank

Abstract: This study aimed to assess how the contamination rate of organ-cultured corneas has evolved and to analyze the evolution of microorganisms involved.Methods: Data from the Besançon eye bank were reviewed over 14 years (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). The changes in the contamination rate and the contaminant species found during the organ culture storage were analyzed. Microbiological tests were performed twice on the storage media-at day 5 and before the desw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…The New Zealand Eye Bank Study reported 1% microbiological contamination between 2000 and 2009 (Cunningham et al., 2012). Data from a French eye bank between 2005 and 2018 reported an average annual contamination rate of 6.8% (Fabre et al., 2021). In a study by the Eye Bank of Rome, contamination was detected in 67% of donated corneas (Vignola et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The New Zealand Eye Bank Study reported 1% microbiological contamination between 2000 and 2009 (Cunningham et al., 2012). Data from a French eye bank between 2005 and 2018 reported an average annual contamination rate of 6.8% (Fabre et al., 2021). In a study by the Eye Bank of Rome, contamination was detected in 67% of donated corneas (Vignola et al., 2018).…”
Section: Discussionmentioning
confidence: 99%